Impacts and requirements of globalization on statutory interpretation in Vietnam - Pham, Thi Duyen Thao (Đại học Quốc gia Hà Nội, 2020)
The official empowerment of SI when applying the law at the Court is currently the ultimate solution. SI Court will be able to comprehensively solve the problems of the law when applying in accordance with the nature of SI, at the same time overcome the shortcomings of SI work in recent years in Vietnam: while the subject with the right of SI is very limited and they do not implement the law, the entities that conduct SI regularly have no authority and necessary implementation mechanism. Because the Standing Committee of the National Assembly currently administers the legislature, the executive and the judiciary to conduct the SI, the result is mainly legislative and law-making oriented.